Growth and Development in Extremely Low Birth Weight Infants After the Introduction of Exclusive Human Milk Feedings - Colacci, Michael; Murthy, Karna; DeRegnier, Raye-Ann O.; Khan, Janine Y.; Robinson, Daniel T. (American Journal of Perinatology, 2017)
Objective To estimate associations of exclusive human milk (EHM) feedings with growth and neurodevelopment through 18 months corrected age (CA) in extremely low birth weight (ELBW) infants.Study Design ELBW infants admitted from July 2011 to June 2013 who survived were reviewed. Infants managed from July 2011 to June 2012 were fed with bovine milk-based fortifiers and formula (BOV). Beginning in July 2012, initial feedings used a human milk-based fortifier to provide EHM feedings. Infants were grouped on the basis of feeding regimen. Primary outcomes were the Bayley-III cognitive scores at 6, 12, and 18 months and growth.Results Infants (n = 85; 46% received EHM) were born at 26 ± 1.9 weeks (p = 0.92 between groups) weighing 776 ± 139 g (p = 0.67 between groups). Cognitive domain scores were similar at 6 months (BOV: 96 ± 7; EHM: 95 ± 14; p = 0.70), 12 months (BOV: 97 ± 10; EHM: 98 ± 9; p = 0.86), and 18 months (BOV: 97 ± 16; EHM: 98 ± 14; p = 0.71) CA. Growth velocity prior to discharge (BOV: 12.1 ± 5.2 g/kg/day; EHM: 13.1 ± 4.0 g/kg/day; p = 0.33) and subsequent growth was similar between groups.Conclusion EHM feedings appear to support similar growth and neurodevelopment in ELBW infants as compared with feedings containing primarily bovine milk-based products.
Keywords: human milk fortifier; preterm; infant; growth; development